Optical Digital Communication System in Open Space without Own Electromagnetic Emission - Krzysztof SZAJEWSKI; Tomasz PAŁYS; Anna SZAJEWSKA (Communications of International Proceedings, 2024)
UAV (Unmanned Aerial Vehicle) communication in operational conditions requires reliable, safe and undetectable solutions. Traditional radio systems are susceptible to interference, and optical FSO (Free-Space Optics) technologies require complex beam control mechanisms, which limits their use in lightweight UAVs. The key motive of the study was to develop a new communication system that minimizes these limitations, improving the safety and efficiency of transmission. The literature indicates a lack of solutions that would combine the advantages of FSO technology, such as high throughput and resistance to electromagnetic interference, with the possibility of use in lightweight UAVs without heavy control mechanisms. The gap primarily concerns the lack of technology enabling emission-free communication, which would be both simple to implement and adapted to changing weather conditions. As part of the study, an innovative system based on a piezoelectric optical modulator was developed. The methodology included designing and analyzing the possibilities of a modulation system based on an optical cone with variable geometry. The system works by illuminating the UAV with a laser beam from a ground station, which is modulated and reflected back, eliminating the need for the UAV to emit its own radiation. Theoretical analyses of the communication range and the effect of wavelength on transmission efficiency were conducted. The results indicate that the system can reach significant distances. The solution is characterized by high resistance to detection and interference, making it a promising direction for the development of FSO technology for UAVs.
Keywords: Free space optical; modulating retroreflector; corner cube retroreflector.